Growing together Towards a more inclusive Ireland - Haugh, David (OECD Publishing, 2016)
The Irish economy is growing strongly, but there is a risk many households will be left behind despite robust growth. High joblessness especially among the low-educated and skill-biased wage differentials have induced high market income inequality, among the highest in the OECD. Ireland's comprehensive welfare system provides a broad range of social benefits, which keeps jobless households out of poverty, but this reduces the financial incentives to work, especially for families with children. Structural unemployment is also explained by the lack of skills required to find employment in the Irish labour market, where the presence of multinational enterprises increases the reward for high skills and the penalty for poor skills. With the unemployed pool lacking the right skills and financial incentives, employers tend to resort to foreign workers, a practice facilitated by the well-functioning migration system. Getting more people into work is important to share the benefits of the recovery as widely as possible. This requires building up work capacity, especially by improving jobseekers' training, and ensuring welfare recipients honour their Job Path commitments in return. More needs to be done to increase incentive to work by reducing welfare and low-income traps. This should be done by shifting the tax burden from labour to indirect taxes in a progressive way that does not harm the lowest income groups. (www.oecd.org/eco/surveys/economic-survey-ireland.htm)
Keywords: Employment; Economics